The historiography on Domitian in three acts: traditional, revisionist, and rhetorical perspectives (19th-21st centuries) - de Sousa Cotrim, Irlan (Romanitas - Revista de Estudos Grecolatinos, 2025)
In this article, we propose an analysis of the representations of Emperor Titus Flavius Domitian (81-96) in the texts of antiquarian historians confined to the 19th, 20th, and 21st centuries. We identify three perspectives on this controversial Princeps. In the period spanning from the late 19th century to the mid-1930s, the traditionalist perspective stands out, wherein, despite its proponents recognizing the importance of material culture in historical analyses, primacy is still given to textual sources. In the second phase, between the mid-1940s and 1989, revisionist texts emerge, in which the characterization of tyranny, inherited from the traditionalists, began to be questioned by historians through the exploration of material culture. Finally, in the rhetorical perspective, which unfolds between the 1990s and the first two decades of the 21st century, historians and classicists are observed to understand the rhetorical construction of both textual sources and material documentation.
Keywords: Domitian; Historiography; Tyranny; Blame